Effect of Mixing Methods on Mechanical Properties of Alginate Impression Materials - Gary Frey, DDS;1 Huan Lu, DDS, PhD;1 and John Powers, PhD2 (Journal of Prosthodontics, 2005)
A commercial mechanical mixer is available to make the mixing of alginate more convenient and more consistent for the practitioner; however, there is very little information on the mechanical properties of alginate mixed with this device as compared with hand mixing.